The Level Performace Analysis of Service: A Case of Jalan I Gusti Ngurah RAI, Jakarta - Chrystin Indah Novitasari; Andri Irfan Rifai; Adinda Fajarika Akhir (Indonesian Journal of Multidisciplinary Science, 2022)
Jalan I Gusti Ngurah Rai, which is located in the Administrative City of East Jakarta, is one of the areas with quite crowded visitors because it is one of the access roads connecting Bekasi City to Jakarta, and there is a train station and TransJakarta bus stop which is a travel accommodation to the destination. This study aims to determine the level of pavement service performance on the Jalan I Gusti Ngurah Rai section, East Jakarta. This research was conducted using a questionnaire instrument distributed through a google form. The analysis method used in this study is Importance Performance Analysis (IPA) by comparing the satisfaction and importance values of pedestrians passing through the sidewalk. The results showed that the average pedestrian interest index was 4.44, the average service index was 4.03, and there was an average GAP for each variable of -0.42. From the processed data, it was concluded that the performance of the pavement service level could be categorized in class A with some maintenance that needs to be improved.